Neuropsychological sequelae in Kleine-Levin syndrome: case report - FONTENELLE,LEONARDO (2000)
Kleine-Levin syndrome is characterized by periodic hypersomnia, hyperphagia, sexual disinhibitions and behavioral disturbances. The prognosis is generally benign, with normal cognitive and social functions after the episodes. We describe a typical case of Kleine-Levin syndrome associated with apparent academic decline, neuropsychological sequelae and personality alterations after the second episode of the illness. Further research in the natural history of Kleine-Levin syndrome is needed, for example, to determine whether early intervention would improve long-term prognosis.